Saudi Arabia : 2018 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
Reform momentum remains strong under Vision 2030. New reform initiatives are being rolled-out under the Vision Realization Programs (VRPs). Oil prices have risen over the past year and are positively affecting fiscal and external balances. Higher oil prices provide both an opportunity and a risk to the fiscal reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet